Business Model Canvas : Merella / Maisarah Abdul Rashid - Abdul Rashid, Maisarah (2020)
Merella is a hand-free umbrella where make the user’s both hand free such as hikers and travellers. Their hand need to be free because they using all their energy to get to the destination. Next, our product customer are people who always busy with their phone and for those who needs to carry many things including the umbrella. This is because, Merella can protect both the users and their belongings in the waterproof backpack to make it safer. Students also can use Metrlla since it is affordable to everyone